Planar polarity: converting a morphogen gradient into cellular polarity. - Collu, G.M.; Mlodzik, M. (Current Biology, 2015)
Epithelial cells are polarized within the apico-basal and planar axes. The latter - planar cell polarity - requires long-range regulation of orientation as well as short-range, cell-to-cell realignment through feedback loops. New insights into the long-range, gradient-type regulation reveal how a kinase translates the morphogen gradient input into cellular orientation.